1990
DOI: 10.1212/wnl.40.6.897
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism due to a basal ganglia lacunar state

Abstract: We report a patient with a clinical syndrome indistinguishable from Parkinson's disease in which postmortem examination revealed extensive lacunar infarction of the basal ganglia without evidence of coexistent Parkinson's disease. This case provides pathologic confirmation of the concept of vascular parkinsonism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
62
1
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 0 publications
8
62
1
4
Order By: Relevance
“…The exact pathophysiological mechanisms leading to VP are unknown, although diffuse white matter lesions may damage the net thalamocortical loop, thereby decreasing the ultimate influence of the basal ganglia on higher centers of motor planning and execution. All the same, strategic infarcts would cause parkinsonism by disrupting the putamino-pallido-thalamic loop 1,35 . Notwithstanding the clinical variability, neuroimaging is also problematic.…”
Section: Discussionmentioning
confidence: 99%
“…The exact pathophysiological mechanisms leading to VP are unknown, although diffuse white matter lesions may damage the net thalamocortical loop, thereby decreasing the ultimate influence of the basal ganglia on higher centers of motor planning and execution. All the same, strategic infarcts would cause parkinsonism by disrupting the putamino-pallido-thalamic loop 1,35 . Notwithstanding the clinical variability, neuroimaging is also problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of the patients with PD p resented vascular lesions in the periventricular white m a t t e r, lesions were also found in the basal nuclei and subcortical white matter, which made it a comp l e m e n t a ry exam in the etiology of the conditionuseful for the confirmation and localization of vascular lesions and exclusion of other causes for symptom a t o l o g y, but didn't help in obtaining a diff e re n t i a l diagnosis for PD and VP 2,4,12,20 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the nigrostriatal dopaminergic nerve terminals within the striatum are highly vulnerable to ischemia [11], and the concentration of L -dopa is reduced in the cerebrospinal fluid from patients with suspected VP as well as IPD [63]. This may in part explain the initial transient response to L -dopa in some present patients with SLP or CWMH without 4- to 6-Hz tremor and cogwheel rigidity and in reported cases with vascular lesions without evidence of coexistent IPD at autopsy [6, 15, 44]. On the other hand, parkinsonism in cases with CWMH may be produced through disconnection of the basal gray matter (corticostriatal and thalamocortical tracts) and cerebellum from the supplementary motor area [18]as has been assumed in cases with hydrocephalus [64, 65]and Binswanger’s disease [18, 66].…”
Section: Discussionmentioning
confidence: 99%
“…In 1929, Critchley [1]designated such cases as ‘arteriosclerotic parkinsonism’, reporting its clinical characteristics as compared to idiopathic Parkinson’s disease (IPD) consisting of rapid progression, symmetrical symptoms, absence of tremor and plastic rigidity instead of cogwheel rigidity. While he related the symptoms to vascular changes in the globus pallidus and, to a lesser extent, the substantia nigra, later autopsy- or neuroimaging-based studies have related parkinsonism to symmetrical vascular lesions in the putamen [2, 3, 4, 5, 6, 7]or cerebral white matter [8, 9, 10]. Experimental and human autopsy studies have demonstrated that dopaminergic nerve terminals [11], GABA/substance P neurons (which give rise to the indirect pathway [62]) [12], dopamine receptors [13]and nicotinic acetylcholine receptors [14]in the striatum are highly vulnerable to ischemia, which may result in an increased susceptibility to parkinsonism.…”
Section: Introductionmentioning
confidence: 99%